Environmental conditions limit attractiveness of a complex sexual signal in the túngara frog. Issue 1 (December 2017) - Halfwerk, Wouter; Smit, Judith; Loning, Hugo; Lea, Amanda; Geipel, Inga; Ellers, Jacintha; Ryan, Michael
Abstract Animals choosing particular display sites often balance sexual and natural selection pressures. Here we assess how physical properties of display sites can alter this balance by influencing signal production and attractiveness of the túngara frog (Physalaemus pustulosus ). Males that call from very shallow water bodies (few mm depth) benefit from reduced predation risk, but by manipulating water levels, we show that this comes at a cost of reduced attractiveness to females. Our data show that calling from shallower water reduces a male's ability to float, limits the inflation of his vocal sac, and consequently reduces signal conspicuousness in terms of amplitude and complexity. Our results demonstrate that display site properties can set limits on signal production and attractiveness and may hence influence signal evolution. Signallers may shift between sites or engineer their display location, which can play a crucial role in signal divergence and speciation, particularly in a rapidly changing world. Animal sexual signals should be conspicuous to mates but not to enemies. Here, the authors show that call site properties can set limits on the attractiveness of male frogs' advertisement call, but that males may balance sexual success over predation risk by digging deeper puddles.